“Talk to strangers!” Omegle and the political economy of technology-facilitated child sexual exploitation - Salter, Michael (Journal of criminology, 2024)
This article examines how technology-facilitated child sexual exploitation has flourished within the laissez faire regulatory frameworks of neoliberalism, and argues that political economy should play a more central role in theorising about child sexual abuse. Drawing on the case study of Omegle, a livestreaming website that matches strangers via webcam, the paper illustrates how deregulatory trends have produced an alignment between the sexual interests of child sexual abusers and the economic interests of some online service providers. The paper suggests that intersecting political ideologies and economic structures have increased opportunities for child sexual exploitation and decreased formal and informal controls, while recruiting paedophilic desires and exploitative subjectivities within processes of capital accumulation. The paper explores the implications of political economy for theories of child sex offending, which have typically focused on the psychological, social and legal dimensions of child sexual abuse while overlooking the role of capitalist structures and imperatives.